Spatial Metonymy in Balinese Language: Semantic and Syntactic Perspectives - Susini, Made; Kasni, Ni Wayan; Sujaya, Nyoman (International Journal of Psychosocial Rehabilitation, 2020)
--This study reveals metonymy as a language phenomenon related to language manipulation in communication. By this form of language certain entity is used to replace other entity to refer to something and the two entities have a relationship of contiguity. Based on the type of entity used, metonymy is of three types among those are spatial, temporal, and abstract metonymy. Spatial metonymy uses spatial entities and these entities are related to physical entities that have spatial extensions and can be in three-dimensional space. Applying Seto’s E-relation metonymy concept (1999), Halliday’s grammatical metaphor (2009), and Halliday& Matthiessen’s structure of transitivity (2014), semantically this research is to investigate the types of spatial metonymy found in Balinese language and syntactically to explore them from transitivity structure perspective. The data sources of this research are books of Balinese short stories. Biernacka’s procedure was applied to identify metonymy and functional grammatical analysis method to analyze the transitivity structure of the clauses under study. From semantic perspective, the spatial metonymy found in Balinese has the following reference types: 1) the whole-part type, 2) the container-contents type, and 3) the adjacency type). The whole-part types include: a) object-component type, b) organization-member type, and c) object-material type. From transitivity structure view point, incongruent structure is only found in two types of spatial metonymy which include organization-member type and object-component type. A metonymic construction does not always imply that it has incongruent grammatical realization.